Competency-based education programs in Texas : an innovative approach to higher education. - Daugherty, Lindsay; Davis, Van L.; Miller, Trey (Research report (Rand Corporation) ;, 2015)
"This report aims to describe existing competency-based degrees and certificate prgorams in Texas; to summarize the national landscape for competency based programs, including the perceived benefits and limitations; and to suggest some potential areas for focus as the state of Texas and higher-education institutions explore the possibility of further expanding these programs"--Preface